2022
DOI: 10.3390/children9070947
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Guided Surgery (FGS) during a Laparoscopic Redo Nissen Fundoplication: The First Case in Children

Abstract: We present the first case of fluorescence-guided surgery (FGS) using indocyanine green (ICG) in a pediatric redo-Nissen fundoplication. The patient is a 17-year-old male with recurrent gastroesophageal symptoms who underwent primary antireflux surgery at 10 months of age. During the redo fundoplication, ICG was intravenously administered to help the visualization during the adhesiolysis between liver, stomach and right crus of the diaphragm and to spare small oesophageal vessels and the left gastric artery. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…ICG fluorescence imaging was used to identify and manage insufficient graft perfusion in a boy who underwent liver transplantation [ 19 ]. In one case, fluorescence helped to detect the blood supply during a re-do Nissen [ 20 ] and, in another case, it was useful to validate blood perfusion of the esophageal wall and anastomotic site during esophageal atresia repair [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ICG fluorescence imaging was used to identify and manage insufficient graft perfusion in a boy who underwent liver transplantation [ 19 ]. In one case, fluorescence helped to detect the blood supply during a re-do Nissen [ 20 ] and, in another case, it was useful to validate blood perfusion of the esophageal wall and anastomotic site during esophageal atresia repair [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 0.125 mg/kg of ICG was infused to achieve visualization of the operative field in the case of re-do Nissen [ 20 ]. The dye was intravenously administered during surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clearance rate decreases subsequently, it is cleared quickly enough to allow multiple injections in most procedures. Despite a paucity of clinical studies evaluating its role in esophagogastric pediatric surgery, FGS has shown promising results in helping guide TEF (13) or thoracic duct identification (15) and improving the accuracy of anatomical delineation in EA repair procedure (11) and redo funduplication surgery (16). The administration of ICG sprayed through the trachea into the fistulae, which had not been previously described, allowed the identification of recurrent TEFs eliminating the need for guide wire placement, which can save anesthesia time and reduce tissue damage (13).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Regarding fundoplication surgery, Paraboschi et al described that the use of intraoperative ICG helped to identify the esophagogastric junction's main landmarks, which are usually altered in patients with a previous surgery. 16 They reported a 17-year-old male with recurrent gastroesophageal symptoms who underwent primary antireflux surgery at 10 months of age. Intravenous single dose of ICG (0.125 mg/kg) was injected 1 minute before imaging to achieve optimal dye performance.…”
Section: Esophagogastric Surgerymentioning
confidence: 99%